Effect of Leadership Styles of School Principals on Organizational Citizenship Behaviors - Avcı, Ahmet (Academic Journals, 2016)
The aim of this research is to investigate the relationship between the leadership styles of principals and organizational citizenship behaviors of teachers according to teachers' perceptions. In this research, a relational survey model was used. Data for the research were obtained from 1,723 teachers working in public and private schools which were subject to Ministry of National Education in the Kadikoy district of Istanbul province in 2014. In this research, data were collected through "Personal Information Form" developed by the researcher, and "Effects of Leadership Styles of Principals on Organizational Citizenship" inventory consisting of "Leadership Styles Scale" and "Organizational Citizenship Scale". The inputs of data obtained from respondents were entered via SPSS 17.0; data of the research were analyzed by "average", "standard deviation", "Pearson correlation coefficient moments" and "regression analysis". According to the analysis results obtained in the research, teachers' average perceptions regarding the transformational and transactional leadership characteristics of principals and the average of acting in organizational citizenship behavior were high. There was a positive highly significant relationship between the transformational and transactional leadership characteristics of principals and the organizational citizenship. Transformational leadership positively affects the level of organizational citizenship more than transactional leadership.
Keywords: Leadership styles; Organizational citizenship behavior; School culture